Site planning for Gudawang Karst Caves, Bogor, Indonesia / Andrianto Kusumoarto, Rahmat Rejoni and Joko Mijiarto - Kusumoarto, Andrianto; Rejoni, Rahmat; Mijiarto, Joko (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, Selangor, Puncak Alam campus, 2017)
The Gudawang Karst Caves Area (GKCA) is a potential area to be developed as a special interest ecotourism destination area and caves conservation ecotourism area. GKCA located in Cigudeg, Bogor Regency. The purpose of this research is to make site plan on GKCA development for ecotourism destination. There are three caves of Si Masigit Cave, Si Menteng Cave, and Si Pahang Cave. Based on the analysis of carrying capacity, the maximum number of entourage entered the cave is less than ten people with a maximum time limit of 20-30 minutes. Based on the site analysis, the area can be developed are the area for special interest ecotourism activities (caves), buffer area activities, and cave conservation area activities